Major Power in the Making: Analisis Komprehensif Status Indonesia dalam Hirarki Politik Internasional, 2014-2024 - Rosyidin, Mohamad; Kusumawardhana, Indra (Andalas Institute of International Studies UNAND, 2023)
Indonesia’s status as a middle power has become a commonsense in contemporary International Relations (IR) literature. Existing scholarships on this topic rely on a behavioral approach, emphasizing foreign policy characteristics in defining Indonesia’s status. Other scholars employ a material approach, measuring Indonesia’s economic as well as military capabilities. Previous studies have tended to overlook social and psychological elements of Indonesia’s international standing. This paper argues that Indonesia’s status cannot be determined by partial perspectives. Rather, it requires a comprehensive analysis by incorporating material, behavioral, social, and psychological elements to determine Indonesia’s status at the global level. Based on a comprehensive analysis of Indonesia’s foreign policy during Joko Widodo administration (2014-2024), this paper contends that Indonesia can be classified as an intermittent major power, that is, a country that not only aspires to be a major power but also asccending the hierarchy of international politics. In other words, Indonesia is a major power in the making. This idea supports the claim that Indonesia has a great power mentality stemming from its glorious past. This explains why Indonesia’s foreign policy frequently exhibits great power aspirations.